Hadiths on Ahkām al-Usrah and Their Relevance in the Formation of Islamic Family Law - Suhaimi Afan; Maftah Rozani Al-Am (LPPM UIN Syekh Wasil Kediri, 2025)
Islamic family law is the area of law that is closest to the lives of the people and continues to undergo dynamics in line with social changes. The hadiths of ahkām al-usrah, as the second normative source after the Qur'an, play a strategic role in the formation of Islamic family law, but are often understood textually and ahistorically. This study aims to analyse the typology of family law hadiths, explore the substantive meaning of hadiths through the ma‘ānī al-ḥadīs approach, and assess their relevance in the formation of contemporary Islamic family law. This study uses a qualitative method with a literature review approach, analysing family hadiths in authoritative hadith books as well as contemporary Islamic jurisprudence and thought literature. The results show that ahkām al-usrah hadiths have diverse normative functions oriented towards ethical values such as justice, responsibility, and family protection. Through the integration of the ma‘ānī al-ḥadīs and maqāṣid al-syarī‘ah approaches, these hadiths are proven to be relevant and adaptive in responding to the challenges of modern Islamic family law. This study emphasises the importance of contextual reading of hadith as the basis for the formation of Islamic family law that is just and oriented towards public interest.